Jennifer Lammey: capstone - Lammey, Jennifer, artist (Colorado State University. Libraries, 2019)
The artist's statement: Human beings often assign meaning to objects that give the wearer strength or power. For example, an amulet may have been used to ward off the evil eye. Medieval European witch bottles were buried in the ground to trap evil spirits. The objects in this show take the form of my own personal amulets, talismans and vessels. They are a record of obstacles I have overcome, and reminders that in overcoming these challenges, I am stronger as an artist. Unexpectedly, they also helped me discover that my true passion is teaching art to children. Instead of simply telling my students to work through challenges, I now have physical objects to show them what perseverance can look like. For example, I had spent numerous hours on a teapot, but made a miscalculation in the etching process. Instead of abandoning the project I instead repurposed it into a new form, which I call, Teapot, Interrupted. Whenever one of my art students is struggling with an art project I always tell them my teapot story because I believe it is important for students to realize that their teachers make mistakes as well, and are not infallible beings. My goal in sharing my story with my students is to inspire them to take on challenges in their own lives, and to help them learn the value of not giving up even--or especially--when things are at their most difficult.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing